Synthesis of calcium chlorapatite nanoparticles and nanorods via a mechanically-induced solid-state displacement reaction and subsequent heat treatment. Issue 14 (1st October 2017) - Pei, Lei; Tsuzuki, Takuya; Dodd, Aaron; Saunders, Martin
Abstract: A mechanically activated solid-state displacement reaction has been investigated as a means of manufacturing apatite nanoparticles. Mechanical milling and subsequent heat treatment of a CaCl2, Na3 PO4 and NaCl reactant mixture resulted in the formation of chlorapatite nanoparticles embedded within a solid salt matrix. The size and morphology of the chlorapatite nanoparticles was found to depend on the temperature of the post-milling heat treatment. A low temperature of 400 °C yielded largely equiaxed nanoparticles with an average diameter less than 100 nm. In contrast, heat treatment at 775 °C resulted in the formation of chlorapatite nanorods with an average diameter below 200 nm and a [001] growth direction. In both cases, removal of the salt matrix by washing with water gave powders with low levels of agglomeration.